Bupleuri Radix Prevents the Recurrences of Resected Colonic Polyps by Affecting Angiogenin-2-Induced Protein Kinase B/Akt Signaling. (28th October 2020) - Gao, Qiang; Yu, Guihong; Yu, Minghui; Wang, Xinping
Abstract : Aim . We aimed to explore the effects of Bupleuri Radix (BR) on the recurrence of resected colonic polyp (CP) by measuring angiogenin-2-induced protein kinase B (Ang PKB)/Akt signaling. Method . The main ingredients of BR were extracted by using ethanol and measured by HPLC. One hundred twenty patients with CP >10 mm who underwent resected surgery were randomly allocated to an aspirin (AG) or a BR medicine (BG) group. The allocation ratio was 1 : 1 and the intervention duration was one year. The recurrence rate of resected CP was investigated and the plasma levels of Ang PKB/Akt and inflammatory cytokines were measured using ELISA kits. After one-year surgery, side effects were recorded. The relationship between the serum levels of the main compounds of BR and plasma levels of Ang PKB/Akt was analyzed. Results . The main ingredients of CP are paeoniflorin, baicalin, saikosaponin A, and bupleurum saponin B2. Recurrence of resected CP was found in 17 patients from the AG group and eight patients from the BG group after one-year follow-up p < 0.05 . The levels of angiogenin-2 II and PKB/Akt in the AG group were higher than those in the BG group p < 0.05 . Meanwhile, BR treatment reduced the plasma levels of TNF- α, IL-1 β, and IL-6, and increased the level of IL-10p < 0.05 . Inflammatory cytokines are important factors that affect the recurrence of resected CP. Serum paeoniflorin, baicalin, saikosaponin A, and bupleurum saponin B2 in BR had a strong negative relationship with the plasma levels of Ang PKB/Akt. Conclusion . BR significantly reduces the recurrence risk of resected CP by affecting Ang PKB/Akt signaling.